Castleman disease misdiagnosed as immunoglobulin G4-related disease: a case report - Na Li; LiFen Xu; Xiaoxia Liu; Pengjia Wu; Jun Liu; Jiashun Zeng (Frontiers in Immunology)
Castleman disease (CD) and immunoglobulin G4-related disease (IgG4-RD) are rare systemic immune-mediated disorders that share overlapping clinical features, posing significant challenges in differential diagnosis. Here, we present a case of generalized lymphadenopathy initially misdiagnosed as IgG4-RD, which demonstrated a poor response to hormonal therapy. Subsequent pathological biopsy and immunohistochemical analysis ultimately confirmed the diagnosis of CD. This case underscores the limitations of relying solely on serum IgG4 levels as a diagnostic marker to distinguish CD from IgG4-RD. Comprehensive evaluation, including clinical presentation, organ involvement, serological and pathological findings, as well as therapeutic response, is essential to ensure accurate diagnosis and timely management.